194k views
0 votes
Given the equation of the function, write the equation of the inverse, g(x). f(x) = 3x -1

User JohnSUN
by
4.7k points

1 Answer

3 votes

1. Replace f(x) with y:

y = 3x - 1

2. Replace every "x" with "y" and every "y" with "x":

x = 3y - 1

3. Solve for y:

Add 1 to both sides:

x + 1 = 3y -1 + 1

x + 1 = 3y

Divide both sides by 3:

(x + 1)/3 = 3y/3

y = (x + 1)/3

4. Replace y with f−1(x) :

f-1 (x) = (x + 1)/3

User Binwiederhier
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.